Reduction of cAMP and cGMP inhibitory effects in human platelets by MRP4-mediated transport - Borgognone, Alessandra; Pulcinelli, Fabio Maria (Thrombosis and Haemostasis, 2012)
Cyclic nucleotide-dependent inhibition of platelets represents the most important physiological way to limit thrombus formation. cAMP and cGMP increase in platelets as a consequence of prostacyclin and nitric oxide production by endothelial cells and act through PKA and PKG, respectively. The cytosolic concentration of cyclic nucleotides in platelets is regulated by AC- and GC-dependent synthesis and PDE-dependent degradation. In some cells cyclic nucleotides are eliminated also through MRP4/5/8-dependent efflux. As only MRP4 is expressed in platelets, at high levels in dense granules, we determined its role in the elimination of cyclic nucleotides from platelet cytosol. We studied the effects of MRP4 inhibition on cAMP/cGMP effects in platelets. Cyclic nucleotide inhibitory effects triggered by cAMP and cGMP-elevating agents on platelet aggregation are strongly enhanced by MRP4 inhibition and so is cyclic nucleotide-dependent phosphorylation of the common substrate VASP. MRP4 inhibition decreases cAMP concentration in platelet granules and both cAMP and cGMP compete with an established substrate of MRP4 (fluo-cAMP) for entrance in granules. Here we provide the first evidence of the transport of cyclic nucleotides mediated by MRP4 as part of their physiological mechanism of elimination in human platelets, which might represent a novel target to increase cyclic nucleotide-dependent inhibition.
Keywords: Cyclic nucleotides; MRP4; Platelets